(untitled) (Acta Polytechnica CTU Proceedings, 2017)
The paper first describes high speed rail generally and explains the relationship between high speed and conventional railway networks (according to the vehicle types in operation on the network). The core of the paper is comprised of the methodology for choosing the best route for a railway line and its application to the high speed railway connection Praha – Brno. The Algorithm used assumes the existence of more route proposals, which could be different in terms of the operational conception, line routing or types of vehicles used. The optimal variant is the one with the lowest daily cost, which includes infrastructure and vehicle costs; investment and operational costs. The results from applying this model confirmed the assumption, that a dedicated high speed railway line, only for high speed trains, has the same or lower investment costs than a line for both high speed and conventional trains. Furthermore, a dedicated high line also has a lower cost for infrastructure maintenance but a higher cost for buying high speed multiple units.